Double Proteolysis for N- and O-glycan Analysis of Fc-fusion Protein Etanercept - V. G. Varzieva; N. V. Mesonzhnik; A. О. Belushenko; N. L. Bochkareva; S. А. Appolonova (Разработка и регистрация лекарственных средств, 2023)
Introduction. Highly glycosylated proteins are the most abundant class of modern biopharmaceuticals. A majority of such therapeuticals produced by Russian biopharmaceutical companies is biosimilars. The foundation of biosimilar manufacturing is analytical assessment of structure equivalence to an original molecule. Fc-fusions present a challenge due to their structural properties. The only biosimilar of this kind registered in Russia is etanercept – a fusion of tumor necrosis factor receptor α and Fc-fragment of IgG1. Existing approaches widely used in protein analysis do not allow accurate and reliable description of glycoylation of these proteins. Development of new approaches and principles of such analysis is necessary, as the changes in biosimilar’s molecular structure can seriously affect its efficacy and safety.Aim. Development of double proteolysis approaches for glycopeptide mapping of Fc-fusion protein etanercept using Arg-C protease.Materials and methods. Etanercept was subjected to enzymatic hydrolysis using trypsin in combination with Arg-C or Asp-N. The resulting peptides were analyzed using HPLC-MS system Xevo G2-XS QTOF (Waters Corporation, USA). The conformation of glycan structure was performed via analysis of fragment spectra of glycopeptides, acquired with high collision energy mode (MS E ). UNIFI (version 1.8) with biopharmasuetical assessment setting (Waters Corporation, USA) was used to analyze the peptide maps.Results and discussion. It was found that using the combination of trypsin with protease Arg-C leads to reliable results Using the developed approach we successfully determined the majority of O-glycosylation sites and types of O-glycans. It was shown that for an effective O-glycopeptide maping N-deglycosylation stage is required. Most abundant N-glycan structures were identified for each of three N-glycosylation sites (N149, N171, N317). It was determined, that the combination of trypsin with Arg-C allows identification of three-antenna forms despite the presence of O-glycosylation site on the analyzed peptide. General N-glycosylation profile shows comparability of results for both approaches.Conclusion. As a result of this research we developed glycopeptide mapping approaches in which a combination of proteases is used. Using these methods sites of N- and O-glycosilation and glycofoms of etanercept were accurately and reproducibly determined. Developed procedures can be applied to other types of Fc-fusion proteins, making it of broader appeal and benefit to the overall biopharmaceutical industry. These approaches provide comprehensive information useful for structure-function studies and of potential value for product comparability measurements and possibly even future manufacturing control strategies.